2019
DOI: 10.1093/sleep/zsz100
|View full text |Cite
|
Sign up to set email alerts
|

Auto positive airway pressure therapy reduces pulmonary pressures in adults admitted for acute heart failure with pulmonary hypertension and obstructive sleep apnea. The ASAP-HF Pilot Trial

Abstract: Objectives Pulmonary hypertension (PH) is extremely common in acute decompensated heart failure (ADHF) patients and predicts increased mortality. Obstructive sleep apnea (OSA), highly prevalent in congestive heart failure patients, may contribute to further elevated pulmonary pressures. This study evaluates the impact of positive airway pressure (PAP) therapy on PH in patients admitted for ADHF with OSA. Methods A two-center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…8 We also could not demonstrate an influence of SDB on survival or development of CLAD. This could possibly be explained by the relatively short follow-up period but also by an effect of CPAP 4,42,43 Observational studies have demonstrated a beneficial association between CPAP treatment and cardiovascular risk, but randomized controlled trials have failed to verify this association, not only for cardiovascular outcome but also for sympathovagal balance and sleep quality. 44 However, CPAP adherence was not optimal in these trials, 45 but sufficient CPAP adherence seems crucial with regard to cardiovascular outcome as higher adherence rates are associated with better cardiovascular effects, sleep quality, and sympathovagal balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 We also could not demonstrate an influence of SDB on survival or development of CLAD. This could possibly be explained by the relatively short follow-up period but also by an effect of CPAP 4,42,43 Observational studies have demonstrated a beneficial association between CPAP treatment and cardiovascular risk, but randomized controlled trials have failed to verify this association, not only for cardiovascular outcome but also for sympathovagal balance and sleep quality. 44 However, CPAP adherence was not optimal in these trials, 45 but sufficient CPAP adherence seems crucial with regard to cardiovascular outcome as higher adherence rates are associated with better cardiovascular effects, sleep quality, and sympathovagal balance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with SDB and good CPAP adherence had a significantly better survival compared to SDB patients without CPAP treatment. SDB is a known independent cardiovascular risk factor, CPAP treatment can counteract most intermediate pathophysiological traits potentially contributing to cardiovascular disease 4,42,43 . Observational studies have demonstrated a beneficial association between CPAP treatment and cardiovascular risk, but randomized controlled trials have failed to verify this association, not only for cardiovascular outcome but also for sympathovagal balance and sleep quality 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that nocturnal hypoxemia is a potential treating target of sleep apnea in heart failure. Although positive airway pressure ventilation is recommended in some clinical conditions of sleep apnea and has been proven to improve hemodynamic condition and cardiac function, its effect on the prognosis of heart failure patients still remains controversial, especially in those with predominantly CSA . Considering the cost and the tolerance, nocturnal oxygen (NOT) appeared to be an alternative of positive airway pressure ventilation during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea, typically categorized as predominantly obstructive (OSA) or central (CSA), is highly prevalent in both acute decompensated heart failure (ADHF) and chronic stable heart failure . Sleep apnea is responsible for multiple cardiovascular pathophysiological changes in heart failure, such as myocardial ischemia, increased pulmonary arterial pressure, and abnormal cardiac electrophysiological activities, based on complex mechanisms, including nocturnal hypoxemia, increased sympathetic activity, enhanced renin‐angiotensin‐aldosterone system, and chronic inflammation . It has been reported that sleep apnea, generally scored by the apnea‐hypopnea index (AHI), might be an independent risk factor of adverse outcomes in heart failure .…”
Section: Introductionmentioning
confidence: 99%
“…Central sleep apnea (CSA) is a highly prevalent comorbidity in cardiovascular and heart failure patients and is associated with increased morbidity and mortality 1 . Conventional CSA therapies, such as mask‐based ventilation treatment, can alleviate symptoms and lead to positive outcomes, 2,3 but are also associated with limitations of effectiveness due to restricted patient compliance and mask tolerance. In addition, contraindications exist for specific algorithms, such as adaptive‐servoventilation in heart failure patients with reduced ejection fraction 4,5 …”
Section: Introductionmentioning
confidence: 99%